2008
DOI: 10.1152/jn.00956.2007
|View full text |Cite
|
Sign up to set email alerts
|

Probability-Based Prediction of Activity in Multiple Arm Muscles: Implications for Functional Electrical Stimulation

Abstract: Anderson CV, Fuglevand AJ. Probability-based prediction of activity in multiple arm muscles: implications for functional electrical stimulation. J Neurophysiol 100: 482-494, 2008. First published April 24, 2008 doi:10.1152/jn.00956.2007. Functional electrical stimulation (FES) involves artificial activation of muscles with implanted electrodes to restore motor function in paralyzed individuals. The range of motor behaviors that can be generated by FES, however, is limited to a small set of preprogrammed movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 43 publications
(35 reference statements)
8
24
0
Order By: Relevance
“…But the majority of movements we recorded cannot be predicted based on EMG activation patterns alone (>70%) and the same movement can be evoked by activation of different muscles. More extensive surface EMG recordings may not be able to access all of the information necessary to predict movements (Anderson and Fuglevand 2008) and such data may be highly variable by individual (Staudenmann et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…But the majority of movements we recorded cannot be predicted based on EMG activation patterns alone (>70%) and the same movement can be evoked by activation of different muscles. More extensive surface EMG recordings may not be able to access all of the information necessary to predict movements (Anderson and Fuglevand 2008) and such data may be highly variable by individual (Staudenmann et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…To a reasonable degree, the generalized transfer function accomplished this aim for different subjects, different muscles, and for different mechanical situations. Therefore, it would seem that this approach holds promise for use with an algorithm that predicts the EMG activity across multiple muscles associated with desired motor behaviours (Seifert and Fuglevand, 2002; Blana et al, 2008; Anderson and Fuglevand, 2008; Johnson and Fuglevand, 2009; Pohlmeyer et al, 2009). Furthermore, if a patient were equipped with an appropriate interface to the CNS, it seems feasible that kinematic and kinetic features of desired motor behaviours could be identified directly from the cerebral cortex (Wessberg et al, 2000; Serruya et al, 2002; Schalk et al, 2008; Velliste et al, 2008; Pohlmeyer et al, 2009; Hatsopoulos and Donoghue, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we envision a three part system in which (1) recordings of activity from the cerebral cortex provide a moment-by-moment representation of the desired trajectory of the limb (e.g. Georgopoulus et al 1989; Schwartz 1993), (2) the complex patterns of muscle activity associated with the desired limb trajectory are predicted moment-by-moment using probabilistic algorithms (Seifert and Fuglevand 2002, Anderson and Fuglevand 2008, Johnson and Fuglevand 2009), and (3) the predicted patterns of muscle activity are converted to patterns of electrical stimulation that elicit the intended movement. Related to the third part of this system, here we have shown that it is possible, using a generalized transfer function, to accurately reproduce movements (or isometric torque profiles) using electrical stimulation patterns derived from muscle activity patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have reported such methods also (Wessberg et al, 2000; Anderson and Fuglevand, 2008; Fried et al, 2011). In our work, subjects made spontaneous movements and by analyzing the EEG, we could predict movement before its occurrence.…”
Section: Introductionmentioning
confidence: 99%